Quantitative Assessment of Upper Limb Motor Function in Ethiopian Acquired Brain Injured Patients Using a Low-Cost Wearable Sensor - Hughes, Charmayne M. L.; Baye, Moges; Gordon-Murer, Chloe; Louie, Alexander; Sun, Selena; Belay, Gashaw Jember; Zhang, Xiaorong (Frontiers in Neurology, 2019)
Acquired brain injuries place a significant burden on sub-Saharan African rehabilitation clinicians and health care facilities. While wearable sensors have the potential to alleviate these issues, many are beyond the financial capabilities of the majority of African persons and clinics. To bridge this gap, we have developed a low-cost wrist-worn sensor (the outREACH sensor) capable of accurately measuring upper limb movement kinematics. In this study we evaluated the extent to which the outREACH sensor is sensitive to the hand performing the task (unimpaired, impaired) and level of impairment (mild, moderate) in 14 Ethiopian persons with acquired brain injury (mean age = 51.6 +- 12.2 years, 1 female, 13 male). Participants performed an object manipulation task with both the impaired and the unimpaired limb, and reaching performance was measured using standard kinematic measures (i.e., movement time, spectral arc length, peak velocity, peak acceleration, mean velocity, mean acceleration). Overall, movements were smoother and faster when performed by the patient’s unimpaired limb. In contrast, maximum velocity did not differ between the two limbs. Moreover, the outREACH sensor was sensitive to differences in performance-based upper limb impairment. Fugl-Meyer assessment for upper extremity scores were significantly correlated with movement time, spectral arc length, and peak velocity. Upper limb movement kinematics can be accurately measured using the outREACH sensor. The outREACH sensor can be a valuable addition to standardized clinical measures that provides rehabilitation clinicians with information regarding initial upper limb impairment level and changes in function across the rehabilitation lifespan.